EFEKTIVITAS PBL BERBASIS MULTIMEDIA TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA - Judeanto Edy; Ferdy Dungus; Tineke Makahinda (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
The development of technology is increasingly fast, spurring us to be more technology literate, includingin the field of education. This research was conducted to find out how effective the PBL model, based onmultimedia in improving science process skills and student learning result on uniform circular motion,compared to conventional learning. This study uses an experimental method with a pretest-posttest controlgroup design, and data collection techniques use multiple choice questions. The study population was allclass X IPA and with the Simple Random Sampling technique, obtained research samples. Class X IPA 1 asa control class and Class X IPA 3 as an experimental class. Before do the hypothesis test, a normality testand a homogeneity test are first performed. From the results of descriptive analysis, the average value of thecontrol class is 32 and the experimental class is 33. After being given treatment, an average value of controlclass 62 and the experimental class is 79. As for the science process skills, students experience an increasein each assessment indicator. So the use of PBL models based on multimedia, is effective in enhancingscience process skills and student learning result on uniform circular motion.